Bibliotecas versus librerías de grandes superficies comerciales: usuarios y clientes - Ferrer Gimeno, Rosario (Revista General de Información y Documentación, 2007)
This paper deals with the debate that took place in the United States in 1998 regarding the type of libraries that best suited the times. Different critics argued for and against the role of traditional libraries as compared with that of large bookstores. Special attention is paid to the commercial transaction that book loaners effect in some libraries nowadays when they order books and have to pay for the services which they are offered. This new function of libraries whose services are no longer free of charge, is compared in this article to the kind of relationship that is maintained between booksellers and potential buyers of books. Modern libraries tend to offer increasing number of products, often related to new technologies, and the librarian now acts as mediator between these new commodities and their purchasers.